CaMKII Inhibition is a Novel Therapeutic Strategy to Prevent Diabetic Cardiomyopathy - Veitch, Christopher R.; Power, Amelia S.; Erickson, Jeffrey R. (Frontiers in Pharmacology, 2021)
Increasing prevalence of diabetes mellitus worldwide has pushed the complex disease state to the foreground of biomedical research, especially concerning its multifaceted impacts on the cardiovascular system. Current therapies for diabetic cardiomyopathy have had a positive impact, but with diabetic patients still suffering from a significantly greater burden of cardiac pathology compared to the general population, the need for novel therapeutic approaches is great. A new therapeutic target, calcium/calmodulin-dependent kinase II (CaMKII), has emerged as a potential treatment option for preventing cardiac dysfunction in the setting of diabetes. Within the last ten years, new evidence has emerged describing the pathophysiological consequences of CaMKII activation in the diabetic heart, the mechanisms that underlie persistent CaMKII activation, and the protective effects of CaMKII inhibition to prevent diabetic cardiomyopathy. This review will examine recent evidence tying cardiac dysfunction in diabetes to CaMKII activation. It will then discuss the current understanding of the mechanisms by which CaMKII activity is enhanced during diabetes. Finally, it will examine the benefits of CaMKII inhibition to treat diabetic cardiomyopathy, including contractile dysfunction, heart failure with preserved ejection fraction, and arrhythmogenesis. We intend this review to serve as a critical examination of CaMKII inhibition as a therapeutic strategy, including potential drawbacks of this approach.